The effects of short-term glyphosate-based herbicide exposure on insect gene expression profiles - Rainio Miia J; Margus Aigi; Tikka Santtu; Helander Marjo; Lindström Leena (ELSEVIER SCI LTD, 2025)
Glyphosate-based herbicides (GBHs) are the most frequently used herbicides worldwide. The use of GBHs is intended to tackle weeds, but GBHs have been shown to affect the life-history traits and antioxidant defense system of invertebrates found in agroecosystems. Thus far, the effects of GBHs on detoxification pathways among invertebrates have not been sufficiently investigated. We performed two different experiments-1) the direct pure glyphosate and GBH treatment, and 2) the indirect GBH experiment via food-to examine the possible effects of environmentally relevant GBH levels on the survival of the Colorado potato beetle (Leptinotarsa decemlineata) and the expression profiles of their detoxification genes. As candidate genes, we selected four cytochrome P450 (CYP), three glutathione-S-transferase (GST), and two acetylcholinesterase (AChE) genes that are known to be related to metabolic or target-site resistances in insects. We showed that environmentally relevant levels of pure glyphosate and GBH increased the probability for higher mortality in the Colorado potato beetle larvae in the direct experiment, but not in the indirect experiment. The GBHs or glyphosate did not affect the expression profiles of the studied CYP, GST, or AChE genes; however, we found a large family-level variation in expression profiles in both the direct and indirect treatment experiments. These results suggest that the genes selected for this study may not be the ones expressed in response to glyphosate or GBHs. It is also possible that the relatively short exposure time did not affect gene expression profiles, or the response may have already occurred at a shorter exposure time. Our results show that glyphosate products may affect the survival of the herbivorous insect already at lower levels, depending on their sensitivity to pesticides.